An Overview: The Treatment of Tuberculosis - Nitin kumar (Journal of Global Pharma Technology, 2017)
Tuberculosis is an infectious disease which is caused by bacteria. Tuberculosis most commonly affects the lungs, but it can also affect any other organ. The infection doesn`t always result in disease. The human immune defense cells can check and control pathogens, so that progression to disease only occurs in about 10% of adults. However the infection may remain latent and can reactive at any time, also after decades if e.g. the immune system is weakened. If left untreated, tuberculosis is a life-threatening illness. The main burden of tuberculosis is carried by developing countries. The cases of tuberculosis have been declining in Germany for years. But the global increase of tuberculosis affects every region of the world, also developed countries. In the early 1940s and 1950s, tuberculosis (TB) was the number one cause of death. Patients with TB were admitted to the many sanatoria we had in various parts of the country and were often managed by surgical means. TB chemotherapy became available only in the late 1950s. At this time, TB was already a major cause of morbidity and mortality. Realizing its seriousness, the Malaysian government launched its National TB Control Programme (NTP) in 1961. Multi-drug-resistant tuberculosis (MDR-TB) is defined as tuberculosis that is resistant to at least isoniazid and rifampicin: the two most powerful first-line treatment anti-TB drugs. This type of drug resistance, called acquired drug resistance, occurs in TB because a patient’s bacterial population survives for several months during treatment. Keywords: Drug-resistant, Mycobacterium tuberculosis, Ethambutol.